A Unified Research on Advanced Biodegradable Copolymers Based on Their Biodegradable Properties - Dang, Wenyu (Transactions on Environment, Energy and Earth Sciences, 2024)
Recently, biodegradable materials can effectively reduce the environmental hazards. However, they still have limitations in terms of degradation rate and stability. This paper systematically reviews the progress of various biodegradable materials, such as polylactic acid, polyhydroxy-fatty acid ester, polybutylene succinate, and carbon dioxide copolymer. This study found that the degradation rate of polylactic acid can be enhanced through composite methods involving biomaterials. Polyhydroxyl fatty acid esters were synthesized using copolymer preparation, solution pouring, and hot pressing techniques in order to improve their degradation rate. Furthermore, the degradation rate of polybutanediol succinate was improved through composites with biomaterials as well as organic and inorganic materials. Lastly, the degradation rate of carbon dioxide copolymers can be enhanced by utilizing copolymers formed from carbon dioxide monomers along with other polymers or monomers in composite materials. Polylactic acid prepared by the composite method of biological materials can improve the utilization rate of biological resources. The mass preparation of polyhydroxy-fatty acid esters in industry can be enhanced by solution pouring and hot pressing. The composite of polybutanediol succinate and biomaterials improved the mechanical properties. The preparation of carbon dioxide copolymers can improve the utilization of carbon dioxide and reduce greenhouse gases. Most importantly, this research can effectively enhance the degradation performance of biodegradable materials then reducing their impact on the environment.